Anemia relacionada con el consumo de inhibidores de la absorción de hierro en lactantes en el Subcentro Enrique Ponce Luque, Babahoyo. noviembre 2023 - abril 2024. - Garay Alvarado, Hilda Stephania (2024)
Iron deficiency anemia most commonly affects infants 6 to 24 months of age. In Ecuador in 2023, anemia affects 38.2% of children aged 6 months to under 5 months. Iron deficiency anemia is the most common and iron absorption is inhibited by chelators that bind strongly to iron, such as phytates and calcium, preventing its absorption. The objective of this study was to determine the relationship between anemia and the consumption of iron absorption inhibitors in infants at the Enrique Ponce Luque sub-center, Babahoyo. The method used in this research was inductive, the type and design were observational and cross-sectional with the participation of 93 children between 6 and 24 months. The questionnaires applied were the 24-hour reminder in 2 days. The gender was 54.3% female and 45.7% male, 67.4% presented mild anemia and 32% moderate anemia, the age range was 6 to 24 months, the mean consumption was 277.21mg/day for phytate and 757.14mg/day for calcium, in the relation between phytate/iron there was significance (p<0.05) and the relation calcium/iron there was no significance (p>0.05). In conclusion, a significant relationship was found between phytate and iron, and the higher percentage in mild and moderate anemia indicates that there is inhibition; with respect to the calcium/iron ratio, no significance was found.